Letters from the editor lessons on journalism and life - Woo, William F., 1936-2006.; Meyer, Philip (Columbia : University of Missouri Press, 2007)
'A collection of essays by the first person outside the Pulitzer family to edit the St. Louis Post-Dispatch and the first Asian American to edit a major American newspaper. William F. Woo touches on a wide range of subjects to inspire the next generation of journalists'--Provided by publisher.
Includes index.
Description based on print version record.
Keywords: Journalism; Electronic books; Electronic books